Effects of Structured Exercise Programs on Self-Reported Health-Related Quality of Life in Patients with Advanced Non-Small Cell Lung Cancer: A Systematic Review and Meta-Analysis of Randomized Controlled Trials - Carl Lawrence Arenos; Franessa Ysabel Dianne Chan Huan-Jacinto; Josephine Anne Lucero; Frederic Ivan Ting; Marvin Jonne Mendoza; Madelaine Amante; Danielle Benedict Sacdalan; John Paulo Vergara (Journal of Respiration)
Current treatments for metastatic non-small cell lung cancer (NSCLC) have improved survival but remain non-curative, primarily aiming to control disease and to extend life. Structured exercise has demonstrated clinical and quality-of-life benefits in early-stage NSCLC. This systematic review assesses the impact of adjunctive exercise programs on health-related quality of life (HRQoL) in advanced NSCLC patients, with safety as a secondary outcome. Of 1168 studies screened, 13 met the inclusion criteria. All eligible studies were included in the systematic review, and three underwent meta-analysis. Using Synthesis Without Meta-analysis (SWiM), the findings were heterogeneous: four studies showed positive outcomes, two had mixed results, and seven showed negative outcomes. Meta-analysis of studies utilizing the EORTC-C30 tool demonstrated a positive mean difference of 1.57 (95% CI: 0 to 3.14), indicating a trend toward HRQoL improvement. Safety analyses largely revealed no major adverse events related to exercise interventions. Future studies must therefore be designed to account for confounders intrinsic to the underlying disease of study participants to better determine both the efficacy and the safety of structured, adjunctive exercise programs in this patient population.